2010
DOI: 10.1111/j.1530-0277.2010.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of Oral EGCG in a Fetal Alcohol Spectrum Disorder Mouse Model

Abstract: In a murine model, oxidative stress appears to play an important role in ethanol-induced embryonic growth retardation. EGCG can prevent some of the embryonic injuries caused by ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
(48 reference statements)
0
27
0
Order By: Relevance
“…Studies from Yang et al have indicated that maternal green tea EGCG prevents hyperglycemia-induced embryonic vasculopathy and malformation via inhibition of oxidative stress signaling (83). A similar work by Long et al indicated that consumption of green tea prevents ethanol-induced embryonic growth retardation (84). These studies provide insights that a diet rich in chemopreventive compounds consumed early in life may modulate the genetic/epigenetic profiles to confer beneficial effects against the risk of developing several types of diseases later in life.…”
Section: Epigenetic Regulations During Embryogenesismentioning
confidence: 88%
“…Studies from Yang et al have indicated that maternal green tea EGCG prevents hyperglycemia-induced embryonic vasculopathy and malformation via inhibition of oxidative stress signaling (83). A similar work by Long et al indicated that consumption of green tea prevents ethanol-induced embryonic growth retardation (84). These studies provide insights that a diet rich in chemopreventive compounds consumed early in life may modulate the genetic/epigenetic profiles to confer beneficial effects against the risk of developing several types of diseases later in life.…”
Section: Epigenetic Regulations During Embryogenesismentioning
confidence: 88%
“…For instance, peptides that can antagonize ethanol-induced inhibition of L1 cell adhesion molecule have been tested in vitro and in vivo [184,185]; antioxidants, including superoxide dismutase [186], vitamin C [187], vitamin E [188], and green tea extract [189], have been shown to protect against ethanol-induced oxidative stress in FASD animal models. NEURODEVELOPMENTAL DISORDERS in preclinical models.…”
Section: Experimental Treatments For Fasdmentioning
confidence: 99%
“…Reactive oxygen species (ROS) progressed in prenatal alcohol exposure embryos (Henderson et al, 1995; Heaton et al, 2002). Malondialdehyde (MDA) and hydrogen peroxide (H2O2) are linked to nervous injury induced by alcohol (Long et al, 2010; Peng et al, 2005). Yet there are no effective treatments against FASD other than ethanol abstention (Long et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Malondialdehyde (MDA) and hydrogen peroxide (H2O2) are linked to nervous injury induced by alcohol (Long et al, 2010; Peng et al, 2005). Yet there are no effective treatments against FASD other than ethanol abstention (Long et al, 2010).…”
Section: Introductionmentioning
confidence: 99%